Gold(I)‐Catalyzed [8+2]‐Cycloaddition of 8‐Aryl‐8‐azaheptafulvenes with Allenamides and Ynamides: Regioselective Synthesis of Dihydrocycloheptapyrrole Derivatives. Issue 24 (18th March 2021) - Suárez‐Rodríguez, Tatiana; Suárez‐Sobrino, Ángel L.; Ballesteros, Alfredo
Abstract: Gold(I)‐catalyzed higher‐order [8+2] cycloadditions of 8‐aryl‐8‐azaheptafulvenes 1 with allenamides 2 and ynamides 3 were studied. 1, 8‐Dihydrocycloheptapyrroles 4 were achieved by a regioselective [8+2] cycloaddition of azaheptafulvenes 1 and allenamides 2 in the presence of (2, 4‐di t BuC6 H3 O)3 PAuNTf2 as catalyst. Besides, ynamides 3 and 8‐aryl‐8‐azaheptafulvenes 1, undergo a regioselective [8+2] cycloaddition, to give 2‐amido‐1, 4‐dihydrocycloheptapyrroles 7 in the presence of JohnPhosAuNTf2 as catalyst. Both reactions take place with good yields and with a variety of substituents. A plausible mechanism hypothesis suggests a nucleophilic attack of the 8‐azaheptafulvene to the gold activated electron rich allene or alkyne moieties of the allenamide and ynamide, respectively. Abstract : Gold (I)‐catalyzed higher‐order cycloaddition: 8‐Aryl‐8‐azafulvenes undergo a regioselective gold catalyzed [8+2] cycloaddition with electron‐rich allenamines and ynamides to give dihydrocyclohepta[ b ]pyrrole derivatives. The cyclization takes place after the nucleophilic attack of the heptafulvene to the electrophilic intermediates formed by the coordination of cationic gold to either allene or triple bond moieties of the unsaturated systems.